Desenvolvimento de refratários espinelizados avançados eco-amigáveis em substituição aos materiais contendo cromo - Borges, Otávio Henrique (2025)
Until the 1990s, the use of electrofused magnesia-chrome aggregates (EMCA) was widespread in refractory linings for the steel industry. Despite their efficiency and low cost, it was discovered that these materials generate toxic byproducts. Consequently, spinel-containing refractories (MgAl2O4) emerged as the main alternative, though their cost and performance have not yet reached equivalent levels. This thesis combined computational and experimental tools to design and evaluate non-toxic compositions, focusing on their thermomechanical, chemical and microstructural properties. Initially, the substitution of MgO with ZnO as a spinel-forming additive in alumina-based refractory castables was investigated. Its use enhanced the mechanical strength at intermediate temperatures and induced the early formation of zinc spinel (ZnAl₂O₄). However, the Kirkendall effect induced porosity at the alumina aggregate interfaces, highlighting the need for adjustments for steelmaking applications. Additionally, the introduction of zinc oxide enabled microwave-assisted sintering of these materials, an efficient alternative to conventional methods, leading to improved mechanical properties and greater energy efficiency. Nonetheless, zinc volatilization above 1300 °C revealed its limitations in reducing environments. Therefore, the study focused on deeper characterizing the EMCA. Inspired by the findings, four chromium-free compositions were designed and produced via fusion or sintering, both at a laboratory scale. Dilatometry and thermal conductivity tests demonstrated the promising performance of the novel compositions and the potential to tailor their properties through minor compositional adjustments. Finally, the industrial interest in the results of this thesis enabled a partnership with a multinational refractory manufacturer. In collaboration, pilot-scale tests are currently being conducted to develop industry-applicable technology capable of reducing the environmental impact associated with chromium-containing refractories.